The effect of plant extracts on antioxidant potential, microbial and sensory attributes of stirred yoghurt - Tomar, Oktay (Array, 2020)
The aim of this study was to use various plants to increase the functional properties of yoghurt. The ethanol extracts of three different plant (Mentha piperita L., Ocimum basilicum L., and Hibiscus sabdariffa L.) extracts were added to the stirred type yoghurts at different ratios (0.1 %, 0.3 % and 0.5 %). The pH values, colour values, antioxidant activity, microbial and sensory attributes of yoghurt were evaluated on the storage days of 0, 7, 14, 21, and 28. The lowest pH values were found at the beginning (4.29) and at the end (3.95) of the storage period in samples containing 0.5 % hibiscus extract. The addition of plant extracts in amounts of 0.3 % and higher decreased the lightness (L*) value of yoghurt (p<0.05), and the maximum decrease was found in yoghurt samples containing 0.5% hibiscus ethanol extract. The concentrations of added mint and basil extracts increased the yellowness (b*) value (p<0.05), while the addition of hibiscus extract significantly increased the redness value (p<0.05). Hibiscus ethanol extract significantly reduced the growth of total aerobic mesophilic bacteria (TAMB), lactic acid bacteria (LAB) and Lactococcus/Streptococcus bacteria (p<0.05). The antioxidant activity of all samples increased with adding plant extracts. According to the results of sensory analysis, the addition of 0.1 % plant extracts to yoghurts rated higher scores than that of the control sample, but the addition of 0.3 % and 0.5 % ethanol extracts negatively affected the sensory properties. It can be concluded that adding plant extracts had a positive effect on the sensory and functional properties of yoghurt.